PENGARUH PREFERENSI KONSUMEN DAN PERSEPSI KUALITAS TERHADAP LOYALITAS PELANGGAN - Sulistiono, Angga; Alliah, Khalifah Nur (LPPM Institut Bisnis dan Informatika Kesatuan, 2015)
The purpose ofthis study is (1) To determine the Consumer Preferences toward Customer Loyalty. (2) To determine the quality of their perception of the Customer Loyalty. (3) To know the quality of their Consumer Preferences and Perceptions on Customer Loyalty. The number of respondents that weighs the target of this research were 100 respondents to the methodology used is the regression equation and correlation. With the help ofSPSS software version 22.0. The results of this study were (1) the regression equation: Y = -1.491 + 0.389x1 + 0.539x2. This means that all variables have a positive effect on customer loyalty. (2) 34.4% variability explained by the Customer Loyalty and Customer Loyalty Consumer Preferences (R square = 0.343). (3) Consumer preferences have exhibited significantly positive effect on customer loyalty. (4) Perceived Quality has exhibited significantly positive effect on customer loyalty. (5) In a simultaneous regression, Consumer Preferences and Customer Loyalty has a positive and significant impact on customer loyalty. Keywords : Consumer Preferences, Perceived Quality, and Customer Loyalty.